2016
DOI: 10.1007/s10903-016-0444-9
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of IL28B Polymorphism in a Cohort of Italians and Immigrants with HCV Infection: Association with Viraemia, Stage of Fibrosis and Response to Treatment

Abstract: Aims of the study are to investigate, in a cohort of patients affected by HCV chronic hepatitis with genotypes 1 and 4, the prevalence of interleukin 28B (IL28B) genotypes, the possible association between IL28B polymorphism and severity of liver damage, the role of IL28B CC as a predictor of outcome. 365 patients with HCV infection were observed between 2013 and 2014. Demographic, virological, biochemical, and genetic characteristics of each patient were investigated. Liver fibrosis was assessed by transient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
2
1
0
Order By: Relevance
“…Individuals with the CT-TT genotype had a more significant percentage of individuals with liver fibrosis levels of >8.7 Kpa (23.2%). [28] Also, the findings were consistent with those of Mangia et al (2016). They found a significant association between the frequency of IL-28B T alleles and the likelihood of transition to cirrhosis in G1-infected individuals (as detected by biopsy or non-invasive examinations) (p = 0.0018) [29].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Individuals with the CT-TT genotype had a more significant percentage of individuals with liver fibrosis levels of >8.7 Kpa (23.2%). [28] Also, the findings were consistent with those of Mangia et al (2016). They found a significant association between the frequency of IL-28B T alleles and the likelihood of transition to cirrhosis in G1-infected individuals (as detected by biopsy or non-invasive examinations) (p = 0.0018) [29].…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, Nosott et al (2016) found that the association between pretreatment basal viremia levels and IL28B genetic polymorphism (rs12979860) distribution was statistically negligible [28].…”
Section: Discussionmentioning
confidence: 99%
“…To add, there are no reports on polymorphisms of TGF-β1-509, TNF-α-308, and IL10-1082 determining the response to antiviral treatment in HCV patients. SNPs near the IL28B gene encoding IFN-γ on chromosome 19 have been well correlated with the treatment response in HCV which has been well correlated with other American and European studies (Mangia et al, 2016;Nosotti et al, 2017;Thomas et al, 2009;Tipu et al, 2014).…”
Section: Discussionsupporting
confidence: 56%